2017
DOI: 10.7150/ijms.17861
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of heat shock protein 70 and the differential protein expression induced by tumor necrosis factor-alpha enhances migration and inhibits apoptosis of hepatocellular carcinoma cell HepG2

Abstract: Tumor necrosis factor alpha (TNFα) plays diverse roles in liver damage and hepatocarcinogenesis with its multipotent bioactivity. However, the influence of TNFα on protein expression of hepatocellular carcinoma (HCC) is incompletely understood. Therefore, we aimed to investigate the differential protein expression of HCC in response to TNFα stimulus. We observed that HepG2 cell revealed a higher resistance to TNFα-induced apoptosis as compared to the non-tumorigenic hepatocyte THLE-2. By using a label-free qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
(63 reference statements)
0
14
0
1
Order By: Relevance
“…Therefore, investigating a single factor associated with gene regulation is not sufficient to assess the prognosis of patients with HCC. Previous studies have identified genes that regulate HCC progression; however, the majority of these studies focused on single genes or investigated only one of the factors influencing gene regulation (16)(17)(18), without considering their combinatorial effect. To understand the complex molecular biological characteristics of HCC, differentially expressed lncRNAs, miRNAs and mRNAs were identified by analyzing biological datasets from TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigating a single factor associated with gene regulation is not sufficient to assess the prognosis of patients with HCC. Previous studies have identified genes that regulate HCC progression; however, the majority of these studies focused on single genes or investigated only one of the factors influencing gene regulation (16)(17)(18), without considering their combinatorial effect. To understand the complex molecular biological characteristics of HCC, differentially expressed lncRNAs, miRNAs and mRNAs were identified by analyzing biological datasets from TCGA database.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was assessed by MTT assay as previously described . Briefly, cells were seeded at the initial density of 2 × 10 5 cells/well in a 24‐well plate, cultured with serum‐free DMEM for 16 hours, and then incubated with serial concentrations of bergapten (10, 30, and 50 μM) for 24 or 48 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Crude proteins (20 μg of protein) were subjected to a 12.5% SDS‐polyacrylamide gel electrophoresis and transferred onto a nitrocellulose membrane as previously described . The blot was blocked using 5% nonfat milk in PBS, incubated with a primary antibody against specific proteins, and then the bound primary antibodies were detected by peroxidase‐conjugated secondary antibody and ECL chemiluminescence developing reagent.…”
Section: Methodsmentioning
confidence: 99%
“…HSP70 is regulated by the cell cycle and is kept in a low level in normal cells. But in tumor cells, the expression level is increased due to the stimulation by mutant or abnormal proteins [61]. Some research showed that in tumor microenvironment, Hsp70 /Hsp70 complex (HSP70 /HSP70-PCs) plays a complex and important roles.…”
Section: Disscusionmentioning
confidence: 99%